Comparison of personality differences of Polish mountaineers - Piepiora, Paweł; Bagińska, Justyna; Witkowski, Kazimierz; Nakonieczna, Justyna; Piepiora, Zbigniew (Frontiers in Psychology, 2023)
A noticeably increased interest in mountain climbing, both as the form of extreme sport and a form of tourism, has been observed in Poland recently. The assumption of this study is that practicing different varieties of mountaineering influences the personality of Polish climbers in a different manner. The aim of the research was to compare the personality differences of Polish mountaineers. To this aim, the population of Polish high-performance mountaineers was studied (N = 81; including 39 women and 42 men). Due to the type of mountaineering practiced, the respondents were divided into Alpine climbers (n = 48) and Himalayan climbers (n = 33). The average age of the surveyed climbers is 33.85 years. The Big Five model was used including the NEO-FFI Personality Questionnaire and the analyzes were performed using the IBM SPSS Statistics statistical method package, version 27.0. Statistically significant differences were noted only for agreeableness F(1.77) = 5.05, p = 0.027. The Alpine climbers showed a higher level of agreeableness than the Himalayan climbers. After taking into account the Sidak amendment, significant differences in the level of agreeableness were found only among women. Comparisons between other personality traits were not statistically significant. There is a significant difference between the personalities of Polish Alpine climbers and Polish Himalayan climbers in the dimension of agreeableness only among women: female Alpine mountaineers are more agreeable than Himalayan mountaineers. It was presumed that in terms of ethics in the high mountains, the social competences of Alpine mountaineers are much more developed than that of Himalayan mountaineers.